Odpowiedź :
Odpowiedź:
a) (1/4 +3/8) *3= ( 2/8 + 3/8) *3= 5/8 *3= 15/8= 1 i 7/8
b) 2/15 *7 -1/3= 14/15- 1/3= 14/15 - 5/15= 9/15 = 3/5
c) ( 2/3 - 5/12) *7= ( 8/12 -5/12) *7= 3/12 *7 = 1/4*7= 7/4= 1 i 3/4
d) 5/6*7 -3/8 *3= 35/6 - 9/8= 5 i 5/6 - 1 i 1/8= 5 i 20/24 - 1 i 3/24= 4 i 17/24
e) ( 4*3/8+1/16)*2 ( skracamy 4 i 8 przez 4)= 3/2 +1/16= 1 i 1/2 + 1/16=
= 1 i 8/16 + 1/16= 1 i 9/16
f) 2* ( 3/5 - 1/7) +1/5= 2* ( 21/35- 5/35 )+1/5= 2*16/35 +1/5= 32/35 + 7/35=
= 39/35= 1 i 4/35
g) 1 i 1/6 *7 - 5/9 *3( skracamy 9 i 3 przez 3)= 7/6 *7- 5/3 = 49/6 - 10/6=
= 39/6= 6 i 3/6= 6 i 1/2
h) (1 i 1/6 *5-1/3)*5= ( 7/6 *5 -1/3)*5= ( 35/6 -2/6)*5= 33/6 *5=165/6=
= 27 i 3/6= 27 i 1/2
Szczegółowe wyjaśnienie:
Odpowiedź:
(1/4 + 3/8) * 3 = (2/8 + 3/8) * 3 = 5/8 * 3 = 15/8 = 1 i 7/8
(4 · 3/8 +1/16) · 2 = (3/2 + 1/16) · 2 = (24/16 + 1/16) · 2 = 25/16 · 2 =
= 25/8 = 3 i 1/8
2/15 * 7 - 1/3 = 14/15 - 1/3 = 14/45
2 · (3/5 - 1/7) + 1/5 = 2 · (21/35 - 5/35) + 1/5 = 2 · 16/35 + 1/5 =
= 32/35 + 1/5 = 32/35 + 7/35 = 39/35 = 1 i 4/35
(2/3 - 5/12) * 7 = ( 8/12 - 5/12) * 7 = 3/12 * 7 = 21/12 = 1 i 9/12 = 1 i 3/4
1 i 1/6 · 7 - 5/9 · 3 = 7/6 · 7 - 5/3 = 49/6 - 5/3 = 49/6 - 10/6 = 39/6 =
= 6 i 3/6 = 6 i 1/2
5/6 * 7 - 3/8 * 3 = 35/6 - 9/8 = 5 i 5/6 - 1 i 1/8 = 5 i 20/24 - 1 i 3/24 = 4 i 17/24
(1 i 1/6 · 5 - 1/3) · 5 = (7/6 · 5 - 1/3) · 5 = (35/6 - 1/3) · 5 = (35/6 - 2/3) · 5 =
= 33/6 · 5 = 11/2 · 5 = 55/2 = 27 i 1/2